COVID-19 THERAPY: COMPARISON EFFECTIVITY BETWEEN REMDESIVIR AND FAVIPIRAVIR - Nevan Go; Prettysun A Mellow; Bernadette D N Dewi (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2022)
Introduction: Severe Acute Respiratory Syndrome Coronavirus 2 (SARS CoV-2) is the virus that causes Coronavirus Disease 2019 (COVID-19), a disease of global concern(1). Remdesivir and favipiravir are antiviral drugs that are considered COVID19 therapy, as described in Indonesia's 3rd COVID-19 Management Guidelines. They have a similar mechanism, specifically by inhibiting RNA dependent RNA polymerase of the virus (3). Several studies have reported that patients who were treated with these antivirals had a shorter hospital stays (4–6). However, the comparison of efficacy between remdesivir and favipiravir is still unknown.Methods: An observational analytic study was done using a retrospective cohort design. Eighty-eight medical records of COVID-19 patients between January 2021 to August 2021 are collected by consecutive sampling techniques, and this research was carried out at Gotong Royong Hospital Surabaya.Results: Based on the statistical analysis test, there was no clinical improvement difference found, neither patients received remdesivir nor favipiravir based on their clinical manifestations, such as ventilation support and chest X-ray, measured by WHO ordinal scale (p=0,486 ; p>0,05 on the first week and p=0,942 ; p>0,05 on the second week).Conclusions: Improved clinical manifestations were seen in the second week of therapy, either in patients who received remdesivir or favipiravir, but there was no significant effectivity difference between those drugs.